UR_GERICHTE 00/01 20 vom 14. Juli 2000 - UR Obergericht (2000)
Öffentliches Beschaffungswesen. Art. 2, Art. 11 Satz 2, Art. 33 Abs. 1 lit. b, Art. 42, Art. 49 SubV, Ziff. 12 und 18 Anhang II SubV. | Öffentliches Beschaffungswesen. Art. 2, Art. 11 Satz 2, Art. 33 Abs. 1 lit. b, Art. 42, Art. 49 SubV, Ziff. 12 und 18 Anhang II SubV. Ingenieurleistungen für den